Reinvestigating the Wreck of the Sixteenth Century Portuguese Galleon São João: A Historical Archaeological Perspective - Harris, Karen Leigh (University of Pretoria, 2013)
Dissertation (MA (cultural history))--University of Pretoria, 2005.